2016
DOI: 10.2514/1.j054669
|View full text |Cite
|
Sign up to set email alerts
|

Vortical Structures on Three-Dimensional Shock Control Bumps

Abstract: Three-dimensional shock control bumps have long been investigated for their promising wave drag reduction capability. However, a recently emerging application has been their deployment as 'smart' vortex generators, which o↵set the parasitic drag of their vortices against their wave drag reduction. It is known that 3D SCBs produce streamwise vortices under most operating conditions; however, there have been very few investigations which have aimed to specifically examine the relevant flow structures. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…The ellipsoidal working volume measures 130µm in diameter. Paraffin particles, with a diameter of approximately 0.5µm [9], are used to seed the flow. The laser emitting head and receiving optics are mounted on a three-axis traverse.…”
Section: Experimental Methods and Errorsmentioning
confidence: 99%
“…The ellipsoidal working volume measures 130µm in diameter. Paraffin particles, with a diameter of approximately 0.5µm [9], are used to seed the flow. The laser emitting head and receiving optics are mounted on a three-axis traverse.…”
Section: Experimental Methods and Errorsmentioning
confidence: 99%
“…They concluded that the bump height, width and position of the bump peak are the key parameters. Collins et al [9] tested shock control bumps in a wind tunnel, and analysed the performance of shock control bumps at off-design conditions.…”
Section: Shock Control Bumpsmentioning
confidence: 99%
“…It is obvious that 3D bumps can be more easily integrated into the structure of the wing and more easily deformed actively due to their geometrical compactness, considering the potential development of adaptive bumps. Furthermore, 3D bumps also provide the possibility to generate streamwise vortices [15][16][17], which are beneficial for improving the off-design performances, such as buffet alleviation, investigated by Eastwood and Jarrett [18]. Recently, Jones et al [19] investigated the effects of swept flows for 3D bumps, and a new geometric parameter, termed bump orientation, was found to be crucial to the performance under swept flows.…”
Section: Takedownmentioning
confidence: 99%